Anthropic Influence and Heritage Value of the Quaternary Deposits of Rio de Janeiro, Brazil - Pereira, Tainá Paiva; Leite Mansur, Kátia; Goulart Rodrigues, Amanda (Anuário do Instituto de Geociências, 2023)
This study discusses the cause of local lithification in sediments from quaternary beach ridges of Paraíba do Sul Deltaic Complex (Rio de Janeiro, Brazil) and its application to the concept of geological heritage. These beach ridges were excavated to construct the Campos - Macaé Canal, opened in the 19th century predominantly by slave labor. A detailed sedimentological, mineralogical and petrological study was performed. The consolidated material consists to fine-grained sandstone with incipient parallel lamination. Kaolinite associated with iron oxides/hydroxides is organized in thin coatings, sometimes forming meniscus and bridges. The heavy mineral assembly of the sandstone is similar to those found in the beach ridges friable samples. The sandstone granulometry increases from east to west along the canal margins and the same pattern is observed in the adjacent beach ridges. We suggest that pedogenic processes acted intensively on Canal margins after its opening, causing mechanical infiltration and translocation of clay minerals, promoting differentiated consolidation of sediments only in that part that was deepened during the excavation. The anthropic action altered the local physiography by exposing the sediments of beach ridges. Therefore, this sandstone should be considered a geological heritage due to its unique occurrence, touristic, historical, scientific and educational value.